Exploring cultural competence barriers in the primary care sexual and reproductive health centres in Catalonia, Spain: perspectives from immigrant women and healthcare providers - Jone G. Lurgain; Hakima Ouaarab-Essadek; Khadija Mellouki; Sumaira Malik-Hameed; Andleed Sarif; Laia Bruni; Valentina Rangel-Sarmiento; Paula Peremiquel-Trillas (BMC, 2024)
Abstract Background Immigrant populations, especially women, continue facing challenges in accessing quality healthcare, particularly sexual and reproductive health services (SRH). Poor cultural competent health systems contribute to communication challenges between immigrant women and healthcare providers perpetuating health disparities. This exploratory study describes these communication barriers from the perspective of Moroccan and Pakistani immigrant women and healthcare providers within the Catalan health system and its implications to ensure an equitable provision of SRH services. Methods An exploratory-descriptive qualitative study was conducted in various municipalities of Barcelona with high concentration of immigrants. Eight focus groups (N = 51) and semi-structured interviews (N = 22) with Moroccan and Pakistani immigrant women were combined with key informant interviews (N = 13) with healthcare professionals. Thematic analysis and data triangulation were performed primarily using an inductive approach. Results Language barriers and cultural differences in health needs, expectations, care-seeking behaviours and understanding of quality healthcare provision hindered the ability of immigrant women and providers to interact effectively. Limited availability of intercultural mediators and inadequate cultural competence training opportunities for health staff were also identified. Findings suggest a lack of minority representation in the Catalan health workforce and leadership roles. Conclusion This study reinforces the evidence of persistent inequities in accessing healthcare among immigrant populations by focusing on the cultural competence barriers of the Catalan health system in the provision and access to SRH services. The regularization of adequately trained intercultural mediators, quality training in cultural competence for health staff and a commitment to increase workforce diversity would contribute to improve intercultural communication between immigrant patients and providers. An urgent call to action in this direction is needed to ensure an equitable access to SRH services among immigrant women.